Midlife metabolic syndrome and neurocognitive function in a mixed Asian sample. (August 2014) - Collinson, Simon L.; Tong, Sandy J. F.; Loh, Sarah S. K.; Chionh, S. B.; Merchant, Reshma A.
ABSTRACT Background: An association between metabolic syndrome (MetS) and disturbances in neurocognitive function has been identified in Caucasians but the nature and extent of impaired cognition in Asian MetS patients, who may be at greater risk of degenerative cognitive decline, remains unspecified. Methods: A cross-sectional study was conducted at the National University Hospital of Singapore. Participants were recruited from a diabetes clinic at the National University Hospital. Fifty-three patients who met MetS criteria and 44 clinical controls were recruited. All participants were 55 years and above and community ambulant. Neurocognitive function was assessed using the Cambridge Neuropsychological Test Automated Battery (CANTAB). CANTAB performances between MetS and control groups were examined with analysis of variance (ANOVA) and the relative contributions of vascular risk, and intrademographic factors on CANTAB scores were dilineated with stepwise regression analyses. Results: Participants with MetS consistently performed significantly worse than controls across all CANTAB subtests. Education and Chinese race were found to be potential protective factors. Conclusions: Executive and memory impairment is present in Asian patients with midlife MetS who may be particularly vulnerable to the detrimental impact of MetS in midlife.